ANALISA SIMDA-NEXT GENERATION (SIMDA-NG) - Intan Rakhmawati (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
SIMDA is an application used to create documents and reports, related to regional financial management. In 2022, SIMDA Finance V.2.9.0.9 and SIMDA Planning, have been integrated into SIMDA-Next Generation (SIMDA-NG). This study aims to analyze a system that provides convenience and effectiveness in better process of recording and reporting transactions. This type of research is descriptive analytical. The result, In terms of sustainability, SIMDA Finance V.2.9.0.9 provides an effective system for recording and reporting better transactions, because this application is stable. However, in terms of the Electronic Based Government System (SPBE), SIMDA-NG is better, although it is still undergoing updates.